2005
DOI: 10.4088/jcp.v66n0703
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Genetics: A Survey of Psychiatrists' Knowledge, Opinions, and Practice Patterns

Abstract: substantial body of evidence over the past several decades has established that many psychiatric dis-Objective: Knowledge about the genetic basis of psychiatric illness is growing rapidly, and psychiatrists may be called upon to incorporate this information into clinical practice. The goal of this study was to assess psychiatrists' familiarity with and attitudes toward genetic information.Method: We surveyed 844 participants, the majority of whom were psychiatrists, attending a continuing medical education cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
99
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(111 citation statements)
references
References 50 publications
8
99
1
3
Order By: Relevance
“…Although several studies 5,8,13,14 have investigated the role of genetics in practice, consumers only rarely have been asked to share their perceptions of providers' knowledge of genetics and proficiency in the delivery of genetics-related services. In isolation, the conditions represented in this study affect relatively small numbers of individuals, but in the aggregate, these individuals and families constitute a large population that, increasingly often, deftly negotiates the health care system.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies 5,8,13,14 have investigated the role of genetics in practice, consumers only rarely have been asked to share their perceptions of providers' knowledge of genetics and proficiency in the delivery of genetics-related services. In isolation, the conditions represented in this study affect relatively small numbers of individuals, but in the aggregate, these individuals and families constitute a large population that, increasingly often, deftly negotiates the health care system.…”
Section: Discussionmentioning
confidence: 99%
“…The largest survey of psychiatrists' genetic knowledge (n = 352) suggested that practicing psychiatrists may be unfamiliar with aspects of medical and psychiatric genetics relevant to genetic counseling. 40 For a series of questions dealing with general knowledge of genetic principles, psychiatrists answered a median of only 44% correctly, significantly less than a group of genetic counselors and a group of endocrinologists administered the same questions. Psychiatrists also correctly answered a median of only 33% of a series of questions dealing specifically with psychiatric genetics.…”
Section: Who Will Provide Genetic Counseling For Psychiatric Disorders?mentioning
confidence: 99%
“…Psychiatrists recognize the need to incorporate genetics into psychiatric practice (Finn et al, 2005;Hoop et al, 2008), but many lack expertise and/or confidence in this area (Finn et al, 2005;Abbate et al, 2014). Given growing evidence indicating that people with psychiatric disorders and their families would like to receive genetic counseling (DeLisi and Bertisch, 2006;Lyus, 2007;Austin and Honer, 2008;Peay et al, 2009), psychiatry is an area of practice that potentially presents an ideal scenario for fruitful interdisciplinary collaboration between physicians and genetic counselors (Thompson et al 2015).…”
Section: Introductionmentioning
confidence: 99%